Jianpi Huayu Decoction enhances the effect of sorafenib and alleviates adverse events in hepatocellular carcinoma by remodeling the gut microbiota - Xue Deng; Yingjie Xie; Yantong Lu; Xueyan Li; Xuan Guo; Xuhui Huang; Xiaohe Lan; Juze Lin; Wei Tan; Changjun Wang (Elsevier, 2022)
Background: There is an urgent need for effective treatment for advanced hepatocellular carcinoma (HCC). Sorafenib, a multi-kinase inhibitor, is the first-line treatment for advanced HCC, which has a modest efficacy due to severe adverse effects (AEs), acquired resistance, and others. Jianpi Huayu Decoction (JHD) is a traditional Chinese medicine formulation, effective as an alternative and complementary therapy of HCC. Combined sorafenib with JHD is a potential approach to overcome sorafenib resistance. Methods: Effect and AEs of clinical-dose sorafenib combined JHD were evaluated in a subcutaneous model. Diarrhea, the most frequently reported AEs, was evaluated by diarrhea score. Illumina NovaSeq analyzed the gut microbiota (GM) composition of the mice. Results: JHD administration enhanced anti-tumor response to sorafenib and prevented the occurrence of sorafenib-induced diarrhea and body weight loss. Proinflammatory GM Helicobacter positively correlated with sorafenib treatment while anti-inflammatory GM, Muribaculum, Fusicatenibacter, and Dorea positively correlated with JHD treatment. In addition, JHD decreased the infiltration of inflammatory cells and downregulated signaling of interleukin 6/signal transducer and activator of the transcription-3 pathway. Conclusions: Our finding suggested that JHD with microbiota modulation properties could significantly potentiate sorafenib and provide a promising treatment for advanced HCC.